Improving Employee Performance Through Physical Work Environment And Soft Skills: The Moderating Role Of Work Motivation - Erniwati Erniwati; Sardiyo Sardiyo; Mulyadi Mulyadi (UNIVED Press, 2025)
Employee performance is essential for government agencies in achieving organizational goals. Several factors can affect employee performance, including the physical work environment and soft skills, which can be moderated by work motivation. This study aims to analyze the effect of the physical work environment and soft skills on employee performance at the Regional Inspectorate of Musi Rawas Regency, with work motivation as a moderating variable. This research uses a quantitative approach with a survey method. The sample consisted of 65 employees who represented the population in the agency. Data were obtained through questionnaires and analyzed using multiple linear regression and moderation tests. The results showed a significant influence of the physical work environment on employee performance, which is moderated by work motivation. In addition, soft skills also have a considerable impact on employee performance, which is also moderated by work motivation. This research highlights the importance of paying special attention to motivation and soft skills in government agency human resource development programs. A conducive work environment and high work motivation contribute to improved employee performance.